Educational technology 1 - Corpuz, Brenda B., author; Lucido, Paz, I., author (Quezon City : Lorimar Publishing Inc., 2015)
This book is aligned with the National Competency-Based Teacher Education (NCBTS), the standards of good teaching in the Philippines consisting of seven (7) integrated domains, twenty-one (21) strands and eighty (80) performance indicators with the end in view of contributing to the formation of competent and committed professional teachers. It is focused on the development of the 21st century teacher who can respond to the demands of the K to 12 Basic Education Curriculum which the Department of Education began implementing in SY 2012-2013. It is filled with activities which are in keeping with current trends in education such as reflective, integrative, interactivem inquiry-based, brain-based and research-based teaching, constructiveness, multiple intelligences, multicultural education, and authentic assessment.
Includes bibliographical references.
In English text.
Keywords: Educational technology; Technological literacy